Enhancing ornamental marine fish farming through advanced water management with protein skimmers in Lembar, West Lombok - Affandi, Rangga Idris; Azhar, Fariq; Rahmadani, Thoy Batun Citra; Fitria, Syawalina; Agustin, Pradita Ayu; Setyono, Bagus Dwi Hari; Diamahesa, Wastu Ayu; Diniariwisan, Damai; Sumsanto, Muhammad; Abidin, Zaenal (Nur Science Institute, 2025)
The coastal area of Lembar District, West Lombok, has great potential in cultivating marine ornamental fish such as clownfish and blue tang, but water pollution due to Lembar Port activities has caused a decline in water quality and low fish survival. This community service aims to increase the capacity of farmers in managing water quality through the application of protein skimmer technology, a tool that can remove dissolved organic particles from seawater. The activity was carried out in six stages, namely location survey, socialization, training, technology application, mentoring and evaluation, and program sustainability. The results of the activity showed that partners experienced an increase in understanding of the importance of water quality and skills in using protein skimmers. In addition, the condition of the cultivation environment became more stable and supported the growth of ornamental fish. With a participatory approach and the application of appropriate technology, this activity was able to provide a positive impact. This program is expected to be a pilot model for other coastal areas in the development of sustainable marine ornamental fish cultivation.